Desenvolvimento e caracterização de géis Fricke em matriz de PVA-GTA para dosimetria 3D em radioterapia - Alves, Anderson Vinicius Silva (2019)
Three-dimensional dosimetry is one of the most advanced techniques for dosimetry in radiotherapy. The conformed dose administered to radiotherapy results in complex spatial dose distributions, with large dose gradients in small volumes, which makes quality assurance difficult with the traditional methods. Gel dosimetry is a developmental technique based on tissueequivalent gel matrices, which behaves as a continuous three-dimensional dosimeter, preserving spatial information, which can be revealed with imaging techniques. In this research, the methods of producing the Fricke gel with a hydrogel matrix of polyvinyl alcohol cross-linked with glutaraldehyde, its variation of the optical absorption, that allow the dose-response curve to be obtained, its sensitivity, the pre- and post-irradiation stability, and the possibility of ligand and metal ion substitution. The results show that the generated dosimeter has a good sensitivity, with a good linearity range, of approximately 35 Gy, and also good pre- and post-irradiation stability, even under adverse storage conditions. A replacement of ligand and metal ion are promissing. The ligand methylthymol blue showed great potential against the well established xylenol orange.